Report for Sabbatical Leave, Spring 2011. - Piemontese, Luisa (2011)
Studied contemporary poetry in Spanish by Spanish-speaking authors living in Connecticut. Works of four poets were chosen for a bilingual anthology. Seventy five percent of poems selected for this publication were translated and their analytical study completed. In addition, audio interviews were completed, and multimedia presentation, including photos, biographies, and bilingual readings was compiled and given. Publishing companies were identified for submission of the anthology's proposal.
Keywords: Connecticut; Poets; Spanish American; United States; dept.wll; faculty_collection; sabbatical_report

Queering the public sphere in mexico and brazil: sexual rights movements in emerging democracies by rafael de la dehesa - Hernández-Rodríguez, R (The Latin Americanist, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-651-920-888-346 tex.type: [object Object]
Keywords: dept.wll; peer-reviewed

Book Review: Constructing the image of the mexican revolution: cinema and the archive (review) - Hernández-Rodríguez, Rafael (Americas, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/123-344-867-948-97X tex.type: [object Object]
Keywords: book.review; dept.wll; peer-reviewed

Measuring oral proficiency through paired-task performance - Walters, F. Scott (The Modern Language Journal, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/155-184-857-182-107 tex.unique-id: [object Object]
Keywords: dept.wll

The bachelet government: conflict and consensus in Post‐Pinochet chile edited by silvia borzutzky and gregory b. weeks - Cardone, Resha Sophia (The Latin Americanist, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-509-848-727-966 tex.type: [object Object]
Keywords: dept.wll; peer-reviewed